Phương pháp biến đổi Laplace, phép gần đúng điểm yên ngựa độ chính xác cao ứng dụng cho việc tính mật độ trạng thái dao động của các phân tử trong động học của phản ứng đơn phân tử. phần 2 - Quý và cộng sự, Trần Vĩnh (Vietnam Journal of Chemistry, 2014)
In the present paper the number of states and the density of vibrational states, obtained by Laplace transformation method - saddle point approximation (in the previous paper), are used for calculating (by the aid of RRKM theory) the reaction rate constant of 1,1-dicloxiclopropan-2,3-diclopropen isomerization. Results of this process give us all data for drawing the ln(kuni/k¥) - lnP curve (the fall - off curve). This way of investigation, in comparison with others ones (the direct count, Whitten - Rabinovitch methods) appears to have great advantage, because it does not contain internal methodological contraditions and behaviour of the fall - off curve is in very good agreement with experiments.